2018
DOI: 10.1002/ana.25183
|View full text |Cite
|
Sign up to set email alerts
|

[18F]AV‐1451 tau‐PET and primary progressive aphasia

Abstract: [ F]AV-1451binding characteristics differ across the PPA variants and were excellent at distinguishing between the variants. [ F]AV-1451binding characteristics were as good or better than other brain imaging modalities utilized in clinical practice, suggesting that [ F]AV-1451 may have clinical diagnostic utility in PPA. Ann Neurol 2018 Ann Neurol 2018;83:599-611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 49 publications
8
74
0
Order By: Relevance
“…Based on a quantitative analysis of MRI scans relatively close to death and stereologic estimations of AD neuropathology lacking in previous studies of PPA‐AD or DAT‐AD, we found that NFTs, not APs, showed a distribution reflective of the asymmetric aphasic profile that was also significantly associated with cortical atrophy. We show for the first time that NFTs were commensurate with cortical atrophy inside and outside the language network of PPA‐AD (Figure A), which is consistent with the NFT and atrophy relationship measured by tau‐PET (positron emission tomography) in individuals with PPA . Moreover, the asymmetry of only NFTs agrees with previous clinicopathologic relationships reported by our group and others which have shown that NFTs have an anatomical distribution that is mostly concordant with the atrophy and clinical symptoms characteristic of the PPA phenotype .…”
Section: Discussionsupporting
confidence: 90%
“…Based on a quantitative analysis of MRI scans relatively close to death and stereologic estimations of AD neuropathology lacking in previous studies of PPA‐AD or DAT‐AD, we found that NFTs, not APs, showed a distribution reflective of the asymmetric aphasic profile that was also significantly associated with cortical atrophy. We show for the first time that NFTs were commensurate with cortical atrophy inside and outside the language network of PPA‐AD (Figure A), which is consistent with the NFT and atrophy relationship measured by tau‐PET (positron emission tomography) in individuals with PPA . Moreover, the asymmetry of only NFTs agrees with previous clinicopathologic relationships reported by our group and others which have shown that NFTs have an anatomical distribution that is mostly concordant with the atrophy and clinical symptoms characteristic of the PPA phenotype .…”
Section: Discussionsupporting
confidence: 90%
“…Left-hemisphere lateralization of cortical disease has been demonstrated in vivo 10,11 and confirmed qualitatively postmortem, 3 yet righthemisphere disease appears to contribute to language deficits in antemortem imaging of autopsy-confirmed PPA. Furthermore, despite the limited reliability of clinicopathological correlations using PPA syndromic variants, individual clinical features of PPA have only rarely been related to specific anatomic distributions of disease in patients with presumed proteinopathies during life, 17,18 or with a categorical neuropathological diagnosis. Furthermore, despite the limited reliability of clinicopathological correlations using PPA syndromic variants, individual clinical features of PPA have only rarely been related to specific anatomic distributions of disease in patients with presumed proteinopathies during life, 17,18 or with a categorical neuropathological diagnosis.…”
mentioning
confidence: 99%
“…Furthermore, unlike other tau PET tracers, 18 F-AV-1451 is not appreciably blocked by monoamine oxidase B inhibitors (44), ruling out the possibility that the increased 18 F-AV-1451 signal may simply correspond to an increase in monoamine oxidase B induced by the pathologic process (45). In FTD, small but detectable and accurate 18 F-AV-1451 binding has been found in most studies (39,43), and its regional distribution corresponds well to the clinical syndromes (46). The lower 18 F-AV-1451 signal in FTD than in AD could be related to lower 18 F-AV-1451 binding to FTD tau but also reflects the lower tau load in FTD, which is about 10% of that in AD (47).…”
Section: Discussionmentioning
confidence: 87%